High-Accuracy and Low-Cost Attitude Measurement Unit of the CubeSat - Haining Ma; Zhengliang Lu; Xiang Zhang; Wenhe Liao; Klaus Briess (International Journal of Aerospace Engineering)
This paper proposes high-accuracy and reliable attitude measurement methods exclusive for CubeSat with restrictions of low cost, limited space, and low power consumption. The attitude measurement unit is equipped with Commercial Off-The-Shelf (COTS) components including Micro-Electro-Mechanical System (MEMS) gyro and two simultaneously operating star trackers (STR) to enhance the measurement accuracy. The Multiplicative Extended Kalman Filter (MEKF) is used to estimate the attitude of CubeSat, and four kinds of attitude estimation layouts are put forward according to the idea of weighted average of two quaternions from two STR and different architectures of information fusion. Using the proposed methods, the attitude measurement unit can continuously provide accurate and reliable attitude knowledge for attitude control unit when the CubeSat is running in orbit. Numerical simulation is performed to verify the effectiveness of the proposed methods, and it offers a reference for CubeSat developers from the perspective of engineering application.